Incidence of herpes zoster in patients with altered immune function - Chen, S.-Y. (Springer Berlin Heidelberg, 2013)
PURPOSE: To estimate the incidence of herpes zoster (HZ) and rates of post-zoster pain in both the total study population and separately in patients with selected conditions/treatments associated with altered immune function. METHODS: The health administrative claims databases for commercially insured, Medicare, and Medicaid populations, together accounting for approximately 51 million insured individuals, were analyzed between 2005 and 2009 in a retrospective cohort study. Incidence of HZ episodes per 1,000 person-years (PY) was estimated in all study populations as well as within nine potentially immune-altering conditions. Among patients with HZ, the 6-month rate of persistent post-zoster pain was estimated. RESULTS: Analysis of 90.2 million PY at risk revealed that the incidence of HZ in the total study population was 4.82/1,000 PY. The incidence of HZ was highest among patients with bone marrow or stem cell transplant (43.03 %) followed by solid organ transplant, human immunodeficiency virus infection, and systemic lupus erythematosus [95 % confidence interval (CI) 15.19–17.41 %]. HZ incidence rates were higher among persons on immunosuppressants/chemotherapy than among non-users. In the total study population, HZ incidence increased with age (18–49 years: 3.37/1,000 PY; 65+ years: 8.43/1,000 PY; P < 0.01) and female gender (incidence ratio vs. male 1.39, 95 % CI 1.38–1.40 %). The 6-month rate of persistent post-zoster pain was 4.29 % (95 % CI 4.22–4.36 %), which was higher in patients with the selected conditions. CONCLUSIONS: Despite providing a relatively small fraction of overall HZ cases, persons with immune function-altering conditions make a large contribution to the societal healthcare burden because they have a higher risk of developing HZ and persistent post-zoster pain. These risk factors should be considered in HZ prevention efforts.